Development of Writing Anecdote Text Based on Meme Comic Using Interactive Multimedia on Students in Grade 10th of MAS Islamiyah YPI Batangkuis - Tetty Ariyani Nasution; Malan Lubis; Abdurahman Adisaputera (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to determine the results of development of writing anecdote text based on meme comic using interactive multimedia on students in grade 10th  of MAS Islamiyah YPI Batangkuis. Teaching materials is developed in the form of digital modules. This type of research is development research based on the development model of Borg and Gall. With the subject of the trial consisting of material experts, design experts, Indonesian language teachers, and class grade 10th MAS Islamiyah YPI Batangkuis. The results of this study indicate that (1) the validation of the material experts includes the feasibility of the contents expressed very well with a total percentage of 95.5%, the feasibility of presentation was stated to be very good with a total percentage of 90.5%, and the feasibility of the language was stated to be very good with a total percentage of 96%. (2) validation from design experts with criteria is quite good with a total percentage of 78.12%.